SOUND CHANGE MECHANISMS IN ENGLISH AND INDONESIAN: A CONTRASTIVE PHONOLOGICAL APPROACH TO EFL INSTRUCTION - Sulaiman, Masagus; Syahri, Indawan; saputri, kurnia; Tania, Mira (Universitas Muhammadiyah Palembang, 2026)
This study investigates sound change mechanisms in English and Indonesian through a contrastive phonological approach, with the aim of identifying similarities and differences between the two languages, exploring learning difficulties experienced by students, and proposing pedagogical implications for teaching English as a foreign language (TEFL). A qualitative research design was adopted, and the data were collected through documentation techniques and analyzed descriptively. The results reveal two major similarities and three major differences in sound change between English and Indonesian. The similarities involve regressive and progressive sound changes at the single-word level and in prefixation. In contrast, the differences are observed in regressive, progressive, and reciprocal sound changes at the two-word level, in suffixation and circumfixation, which are identified as unfamiliar features that may cause learning difficulties. The pedagogical implications of this study provide practical instructional guidelines for developing more systematic and effective pronunciation practices related to sound change mechanisms.